2021
DOI: 10.3171/2020.6.peds20189
|View full text |Cite
|
Sign up to set email alerts
|

One-year costs of intensive care in pediatric patients with traumatic brain injury

Abstract: OBJECTIVETraumatic brain injury (TBI) is a major cause of death and disability in the pediatric population. The authors assessed 1-year costs of intensive care in pediatric TBI patients.METHODSIn this retrospective multicenter cohort study of four academic ICUs in Finland, the authors used the Finnish Intensive Care Consortium database to identify children aged 0–17 years treated for TBI in ICUs between 2003 and 2013. The authors reviewed all patient health records and head CT scans for admission, treatment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Other studies have reported similar findings showing that healthcare costs, including rehabilitation services for those with GCS 13–15 (mild brain injury), were less than those who had GCS 3–8 (severe brain injury). [ 36 37 ] This is understandable because patients with severe injuries usually need to stay longer in rehabilitation units with higher levels of care.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported similar findings showing that healthcare costs, including rehabilitation services for those with GCS 13–15 (mild brain injury), were less than those who had GCS 3–8 (severe brain injury). [ 36 37 ] This is understandable because patients with severe injuries usually need to stay longer in rehabilitation units with higher levels of care.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 70 million people globally sustain traumatic brain injury (TBI) each year, which can have tremendous socioeconomic impacts on their families and society. However, because of a lack of understanding of the pathobiological mechanisms of TBI, acute and chronic treatment for brain-injured patients has not kept pace.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, due to the developing brain of a child, brain injuries may have a more devastating impact on children than injuries of the same severity have on adults, thus highlighting the need for additional and supplementary treatment options to improve prognosis especially in this population [ 2 , 3 ]. Additionally, long reconvalescence after severe TBI and need for rehabilitation programs are associated with high healthcare costs and, thus, improving treatment after TBI is of high societal relevance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%